619 Plastic Surgery Trauma Operating Theatre: The Impact of a Golden Patient Protocol on Theatre Usage Metrics. (19th August 2022) - Clough, R; Towning, R; Mohan, A
Abstract: Aim: A golden patient protocol was introduced for the dedicated plastic surgery trauma operating list at St Mary's Hospital, London on 05/10/2020. Criteria preferable for golden patient selection included patients with routine anaesthetic requirements, day case surgery, local anaesthetic cases and those requiring the least equipment. The protocol included distribution of a theatre list with a named golden patient the day prior to operating and communication of this to the anaesthetist and theatre co-ordinator. This study sought to determine the effect of this protocol on theatre efficiency and other key metrics. Method: Operation timings were retrospectively and prospectively collected from the hospital Cerner® Surginet database prior to and following introduction of the golden patient protocol, respectively. Fields included were anaesthetic start time, surgery start time, surgery end time and time patient left operating theatre. Statistical analysis was performed using the unpaired t-test method. Result: Data was collected for 73 and 152 operating days before and after the introduction of the golden patient protocol, respectively. Following introduction of the golden patient protocol there was significantly greater mean operations performed per day (2.84 vs 3.29, p=0.0130), reduced mean late start time (34 minutes vs 16 minutes, p=0.0002) and reduced mean overrun time (37 minutes vs 9 minutes, p=0.0001). No significant difference was observed in theatre efficiency (64% vs 67%, p=0.18). Conclusions: Optimising first patient choice and enhancing communication of this with members of the theatre team can result in more procedures being performed and reduced loss of time at the start of an operating list.